The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1651-2227.2007.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self‐reported emotional and behavioural problems in adolescents from Greece and Finland

Abstract: Aim: To compare self-reported emotional and behavioural problems among Greek and Finnish adolescents.Methods: Youth Self-Report scores were analysed for 3373 Greek adolescents aged 18 years and 7039 Finnish adolescents aged 15-16 years from the general population in both countries. The impact of country, gender, place of residence, socioeconomic status (SES) and family stability on the scores was evaluated.Results: Only country and gender yielded small to medium effect on the scores. Greek boys scored signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(58 reference statements)
0
15
0
1
Order By: Relevance
“…Several previous studies have reported cross-cultural differences on YSR-scores but mostly to a lesser extent. For example, in a study comparing adolescents in Greece and Finland, there were higher level of anxiety and depression in Greece but the overall conclusion was that differences between these Northern and Southern regions were small [33]. A study comparing YSR-scores from seven countries also concluded differences were small between countries [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported cross-cultural differences on YSR-scores but mostly to a lesser extent. For example, in a study comparing adolescents in Greece and Finland, there were higher level of anxiety and depression in Greece but the overall conclusion was that differences between these Northern and Southern regions were small [33]. A study comparing YSR-scores from seven countries also concluded differences were small between countries [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are very much in line with the abovementioned ones when it comes to internalizing psychopathology, but we were unable to observe any significant gender difference in the Externalizing scale, and, in fact, girls even reported significantly more aggressive behavior than boys did. This finding is not, however, a new one; the tendency has been reported repeatedly in Finnish community studies [52,53]. Moreover, in a recent cross-national study of more than 8000 adolescents from different Nordic countries, girls reported significantly more anger symptoms than boys did [54].…”
Section: Gender Differences In Descriptive Statisticsmentioning
confidence: 73%
“…Moreover, in a recent cross-national study of more than 8000 adolescents from different Nordic countries, girls reported significantly more anger symptoms than boys did [54]. According to some researchers, this phenomenon may reflect the social, educational and economic gender equality characteristics of Nordic countries [53].…”
Section: Gender Differences In Descriptive Statisticsmentioning
confidence: 99%
“…The results from the ANCOVA were in accordance with previous studies, in which the YSR was used in other countries (Rescorla et al ., 2007; 2012; Fonseca‐Pedrero et al ., ; Milam et al ., ). However, in Greece, boys scored significantly higher in anxious/depressed problems than Finnish girls or boys (Kapi et al ., ). Earlier studies have reported that girls' tendencies to internalize problems were mostly related to the difficulties they experience in their daily lives (Sieh et al ., ).…”
Section: Discussionmentioning
confidence: 97%